Analisis Kesadaran Pelaku UMKM dalam Menyusun Laporan Keuangan : Studi pada UMKM di Kelurahan Tambak Osowilangun Surabaya - Aulia Sayyida Ulfairoh; Ajeng Tita Nawangsari (AKUNTANSI 45, 2025)
This study aims to analyze the level of knowledge and awareness of MSME actors in Tambak Osowilangun Village in preparing financial reports. In Tambak Osowilangun Village, Surabaya, UMKM have great potential to support the local economy. However, there are still many UMKM actors who do not realize how important it is to prepare financial reports systematically. The problem that can be taken is how is the level of knowledge of UMKM actors in preparing financial reports, and how much is the level of awareness of UMKM actors in preparing financial reports. Until now, there has not been much research related to this and previous studies often still analyze more broadly and locations that are not specific. The research method used is descriptive qualitative with primary data from questionnaire results and secondary data based on previous journals. The results show that the level of awareness and readiness of UMKM actors in preparing financial reports is still relatively low. UMKM actors need to make extra efforts to minimize the obstacles faced when preparing financial report.